Percutaneous surgery of allux valgus: risks and limitation in our experience - Cervi, S.; Fioruzzi, A.; Bisogno, L.; Fioruzzi, C. (Acta Biomedica Atenei Parmensis, 2014)
Aim of the study: The Reverdin-Isham percutaneous osteotomy is indicated in the treatment of mild to moderate hallux valgus. The aim of this study is to evaluate the technique itself after a relevant experience. Methods: From January 2010 to January 2012 we have done 213 percutaneous osteotomy. The patients were evaluated clinically and with imaging after a minimum 5 months and a maximum 2 years follow up. For the clinical evaluation it was used the American Orthopaedic Foot and Ankle Society score. Results: The mean postoperatory clinical score was 90 points in front of the mean 45 preoperatory points. The technique was well accepted by the patients because of the minimal invasivity, the poor post operatory pain and the immediate functional recovery even with poor radiological results. These imaging results pose dubts on the lenght of the clinical results and pose the necessity of particular technical choiches and strict indication limits. Conclusion: The results we have obtained with the Reverdin- Isham percutaneous osteotomy have confirmed that this procedure is a valid alternative to other open techniques. However this is a not simple technique, requires the respect of the indications, a steep and long learning curve and the necessity of a greater follow up.